Structural biases in prudential regulation of banks - Tonveronachi, Mario (PSL Quarterly Review, 2009)
The Basle rules produce distortions that are no less serious than those attributed to the former structural regulation. Excessive competition is no less harmful than low competition, the level playing field approach helps the large dimension and "too big to fail" results, capital crunches produce serious effects on the economy while the regulatory costs go on absorbing important resources in small banks. It is a matter for further research to verify if the new approach to regulation has also fostered an increase in the part of GDP absorbed by the financial system without bringing about a better distribution of risks and a proportionate increase in what James Tobin (1984) termed full-insurance efficiency. Paper originally published in the BNL Quarterly Review, vol. 54 n. 219, December 2001, pp. 341-353. JEL Codes: F3, G1, N1, B5